X-ray robot - Allred, Michael (Dark Horse Books, 2020)
Max is a family man seeking a more interesting life. While conducting a new experiment at work the fabric of his reality is torn before his eyes, and a robotic figure appears claiming to be his 277 year-old self. The robot is able to "X-Ray" multiple dimensions and battles a nihilistic entity from another dimension who wants to take all life to its "Pre-Big Bang" status. Max and the robot embark on an interdimensional roadtrip through past and future to take down the "Nihilist" and save the universe!
2010
Keywords: Urknall; Mehrdimensionalität; Roboter; Experiment; Rettung; Weltall; Zeitreise; Wissenschaftler; Robots / Comic books, strips, etc; Time travel / Comic books, strips, etc; Comic